Condensation of delta‐1‐piperideine‐6‐carboxylate with ortho‐aminobenzaldehyde allows its simple, fast, and inexpensive quantification in the urine of patients with antiquitin deficiency. Issue 4 (29th January 2020) - Boehm, Thomas; Hubmann, Holger; Petroczi, Karin; Mathis, Déborah; Klavins, Kristaps; Fauler, Guenter; Plecko, Barbara; Struys, Eduard; Jilma, Bernd
Abstract: Antiquitin (ATQ) deficiency leads to tissue, plasma, and urinary accumulation of alpha‐aminoadipic semialdehyde (AASA) and its Schiff base delta‐1‐piperideine‐6‐carboxylate (P6C). Although genetic testing of ALDH7A1 is the most definitive diagnostic method, quantifications of pathognomonic metabolites are important for the diagnosis and evaluation of therapeutic and dietary interventions. Current metabolite quantification methods use laborious, technically highly complex, and expensive liquid chromatography‐tandem mass spectro‐metry, which is available only in selected laboratories worldwide. Incubation of ortho‐aminobenzaldehyde (oABA) with P6C leads to the formation of a triple aromatic ring structure with characteristic absorption and fluorescence properties. The mean concentration of P6C in nine urine samples from seven ATQ‐deficient patients under standard treatment protocols was statistically highly significantly different ( P  < .001) compared to the mean of 74 healthy controls aged between 2 months and 57 years. Using this limited data set the specificity and sensitivity is 100% for all tested age groups using a P6C cut‐off of 2.11 μmol/mmol creatinine, which represents the 99% prediction interval of the P6C concentrations in 17 control urine samples from children below 6 years of age. Plasma P6C concentrations were only elevated in one ATQ subject, possibly because P6C is trapped by pyridoxal‐5‐phosphate (PLP) blocking fusing with oABA. Nevertheless, both urine and plasma samples were amenable to the quantification of exogenous P6C with high response rates. The P6C quantification method using fusion of oABA with P6C is fast, simple, and inexpensive and might be readily implemented into routine clinical diagnostic laboratories for the early diagnosis of neonatal pyridoxine‐dependent epilepsy.